Snow Music App Demo - Martin, Charles (Zenodo, 2016)
This video shows a demo of Snow Music, a touch-screen musical instrument app for iPad. Snow Music allows performers to interact percussively with field recordings of snow sounds collected in Piteå, Sweden in February 2012. The app also features three backing soundscapes that can be controlled by the switches in the corners of the screen. Revisions in 2014 refined the musical interaction and synthesis systems to allow more expressive performance with a wider range of snow and ice sounds. Visual feedback was also added for the soundscape generators, that is, fading blue and white circles that indicated when the generators had played a note.